Alkali hydroxide-modified Ru/γ-Al2O3 catalysts for ammonia decomposition - Bajus, Stephanie; Agel, Friederike; Kusche, Matthias Manfred; Ní Bhriain, Nollaig; Wasserscheid, Peter (Applied Catalysis A-General, 2016)
We herein present an easy approach to increase drastically the catalytic activity of Ru/ extgreekg-Al2O3 catalysts in ammonia decomposition by surface modification with alkali hydroxides. The best activities have been achieved by a catalyst modification with lithium hydroxide in a Li/Al ratio of 1.7. In contrast, coatings with potassium and caesium hydroxide caused mass transfer limitations in the catalytic material already at low amounts (ratios alkali/Al <0.2–0.3). MAS ssNMR and XRD studies indicate the in-situ formation of alkali aluminates resulting in a basic modification of the support.
EAM Import::2019-03-13
Keywords: Ammonia decomposition; Ruthenium; Alkali doping; Support modification; Lithium aluminate

Enhanced Activity and Selectivity in Catalytic Methanol Steam Reforming by Basic Alkali Metal Salt Coatings - Kusche, Matthias Manfred; Enzenberger, Florian; Bajus, Stephanie; Niedermeyer, Heiko Jannes; Bösmann, Andreas; Kaftan, Andre; Laurin, Mathias; Libuda, Jörg; Wasserscheid, Peter (Angewandte Chemie International Edition, 2013)
Pt on alumina catalysts can be used for converting methanol and water into hydrogen and carbon dioxide, for applications such as hydrogen storage. Both the activity and selectivity could be enhanced by coating these materials with a thin layer of a molten salt mixture of Li/K/Cs acetate. Potassium doping was indentified by DRIFTS measurements to be an important factor for the boost in catalyst performance.

Interface properties and physicochemical characterization of the low-temperature molten salt Li/K/Cs acetate - Deyko, Alexey; Bajus, Stephanie; Rietzler, Florian; Bösmann, Andreas; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry C, 2013)
The surface of macroscopic films of the ternary molten salt mixture Li KCs[OAc] has been investigated by angle-resolved X-ray photoelectron spectroscopy (XPS) as a function of temperature. With increasing temperature a preferential depletion of K is observed by ∼40%. From temperature programmed desorption we find that the onset for the cation desorption follows the order Cs, K, and Li, with activation energies of 125, 148, and 157 kJ mol, respectively; the corresponding value for the [OAc] anion is 147 kJ mol, which is, within the margin of error, identical to the average of the value found for the cations. Ultrathin films of the molten salt deposited on a Au(111) surface by physical vapor deposition show preferential enrichment of Cs, in line with the lower activation energy and thus higher desorption rate of Cs[OAc] from the ternary mixture. Angle-resolved XPS of the molten salt/gold interface demonstrates that the first molten salt monolayer grows in a layer-by-layer growth, followed by three-dimensional island growth at higher coverages. © 2013 American Chemical Society.

Low melting Li/K/Cs acetate salt mixtures as new ionic media for catalytic applications - first physico-chemical characterization - Bajus, Stephanie; Deyko, Alexey; Bösmann, Andreas; Maier, Florian; Steinrück, Hans-Peter; Wasserscheid, Peter (Dalton Transactions, 2012)
In order to expand the temperature limits of Supported Ionic Liquid Phase (SILP) or Solid Catalyst with Ionic Liquid Layer (SCILL) systems to higher operation temperatures, the mixture of lithium acetate, potassium acetate, and caesium acetate (molar ratio of 0.2/0.275/0.525) has been studied in detail. Physico-chemical properties of the bulk melt are reported together with stability data of the modern salt on various solid support materials showing attractive properties for many potential high temperature applications. © 2012 The Royal Society of Chemistry.